Artificial Intelligence Technologies And Their Importance In Ensuring Cyber Security (Eurasian Scientific Herald, 2024)
This article will focus on AI technologies and their role and importance in ensuring cybersecurity. The article examines the aspects of cybersecurity enforcement, information security, and the use of artificial intelligence technologies in cybersecurity